Preparation and Its Adsorptive Property of Modified Expanded Graphite Nanomaterials. (12th February 2014) - Wang, Liqin; Fu, Xiujun; Chang, E.; Wu, Haitao; Zhang, Kun; Lei, Xianchao; Zhang, Ruijun; Qi, Xiaowen; Yang, Yulin
Abstract : Modified expanded graphite (MEG) samples were prepared by strong acid treatment modification. As-prepared MEG samples were characterized by the means of FE-SEM, XRD, FT-IR, N2 physical adsorption measurements, and TG-DTA. The influences of expanded volume and oil viscosity on adsorptive property of MEG samples were investigated. The results suggest that MEG samples have high crystallinity. The pores of MEG samples can be divided into three levels from FE-SEM images. All of the functional groups of MEG samples are nonpolar. The expansion temperature of modified expansible graphite starts at about 700°C. The sorption capacity of MEG increases gradually with expanded volume and oil viscosity increase. When the expanded volume of MEG samples is 320 mL/g, its maximum sorption capacity is up to 84.681 g/g for gear oil with the highest viscosity.